Case report of pyoderma gangrenosum in association with orthopaedic trauma - Jajoria, Hina; Jayan, Jeeno (International Journal of Research in Dermatology, 2022)
Pyoderma gangrenosum (PG) is an uncommon neutrophilic dermatosis characterized by painful skin ulcers. It is associated with various systemic diseases but is rarely associated with orthopedic conditions. We report a case of a pyogenic gangrenosum in a 40-year-old male, that occurred in association with a lower limb fracture. This patient suffered a laceration over the ankle which was the sutured initially and the fracture was managed conservatively. Later on the wound was complicated with the development of pyoderma gangrenosum. Failure to treat with antibiotics and local wound management lead to alternative diagnosis by dermatologist. Patient was successfully managed by dermatologist and fracture was managed conservatively. Such incidents of PG in association with orthopedic procedures, complicate treatment and cause delay in recovery, leading to poor patient outcome.